Lebanon : Report on Performance Under the Program Supported by Emergency Post-Conflict Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This report on Lebanon's Performance Under the Program Supported by Emergency Post-Conflict Assistance analyzes the economic situation and financial system. The economic situation continues to be overshadowed by the political stalemate and episodes of violence. The recent turbulence in international financial markets has not had a significant impact on Lebanon. It is important to restore promptly the revenue source, which constitutes a key measure in the authorities' fiscal adjustment strategy. The ongoing work by the new cash management unit to establish a cash flow plan is encouraging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banque Du Liban; CR; Deposit; ISCR; June; Lebanon